2009
DOI: 10.1016/j.earlhumdev.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of executive function in very preterm and term infants at 8 months corrected age

Abstract: Very preterm infants performed more poorly than full-term infants on measures of EF. Further follow up studies are required to investigate whether EF measures in infancy can predict learning and attention outcome at school age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
3
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 43 publications
5
75
3
4
Order By: Relevance
“…Studies have shown that EF emerge in infancy and continue to develop in adolescence (Sun, Mohay, & O'Callaghan, 2009). The ages of 5-8 years and 11-12 years appear to be milestones in the development of executive components.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that EF emerge in infancy and continue to develop in adolescence (Sun, Mohay, & O'Callaghan, 2009). The ages of 5-8 years and 11-12 years appear to be milestones in the development of executive components.…”
Section: Introductionmentioning
confidence: 99%
“…The age difference may have influenced performance on executive function tasks, as these cognitive processes are still undergoing development during adolescence, and are only fully mature by the end of this period (Lee & Hoaken, 2007;Sun, Mohay, & O'Callaghan, 2009). Therefore, older participants may have an advantage in executive function tasks.…”
Section: Discussionmentioning
confidence: 99%
“…4 There are also modified versions designed to be administered with neuroimaging. 5,6 Considering that executive functions (EF) are a set of higher-order processes that serve to organize behavior and adapt it to context and to individual aims 7,8 and that these functions emerge in infancy and continue to develop through adolescence, 9 there is unquestionably a need for verbal tools to asses EF for clinical and research purposes.…”
Section: Introductionmentioning
confidence: 99%